Community-based ecotourism in rural landscapes: Integrating global sustainability frameworks with local environmental governance - Muhammad Fadhli Fadhillah (Ecotourism and Environment Conservation, 2026)
Background: This study investigates the implementation of community-based ecotourism as a strategy for advancing the United Nations Sustainable Development Goals (SDGs), focusing on its dual role in promoting environmental conservation and strengthening local economic resilience. A fundamental disconnect persists between universal sustainability principles and their practical application within complex local governance systems, creating a critical research gap. Methods: Employing a qualitative case study approach grounded in Ribot & Peluso's (2003) Theory of Access, this research analyzes the intricate power dynamics and access mechanisms within a community-based ecotourism initiative in Sanghyang Kenit, Indonesia. The study deconstructs interactions across a multi-stakeholder network involving PT X, Karang Taruna youth organization, Village Government, and the Citarum Harum Task Force. Findings: The analysis reveals that benefit streams and control over ecotourism commons are governed by dynamic "bundles of power" technology, capital, labor, knowledge, authority, social identity, and relations. These mechanisms create asymmetric governance structures where effective multi-stakeholder collaboration emerges as crucial for balancing conservation and community welfare objectives. The study demonstrates how global sustainability frameworks are reconfigured through local power contests, creating both constraints and opportunities for sustainable outcomes. Conclusion: The research proposes recalibrating institutional arrangements toward polycentric governance models that ensure equitable benefit distribution, enhance managerial flexibility, and standardize conservation practices. Achieving ecotourism's potential requires coordinated action among landholders, policymakers, managers, and tourists to embed global sustainability norms into localized governance structures. Novelty/Originality of this article: This article makes a distinctive contribution to political ecology by applying Access Theory to tourism governance, offering nuanced understanding of how power asymmetries shape the localization of global sustainability frameworks in rural landscapes.